After one hundred years: the 1910 exhibition "Meisterwerke muhammedanischer Kunst" reconsidered - Lermer, Andrea; Shalem, Avinoʿam (Islamic history and civilization, 2010)
Islamic History and Civilization. Studies and Texts straddles the wide world of Islam, from its earliest appearance until pre-modern times, and from its western to its eastern boundaries. The series provides space for diachronic studies of a dynasty or region, research into individual themes or issues, annotated translations and text editions, and conference proceedings related to Islamic history. --Book Jacket